A VERTICAL AND INCLINED EXPLOSION PROTECTION ELEVATOR FOR OFFSHORE PLANTS - KANG, YOUNG GWAN; BAE, JAE SUNG; KIM, MOON SIG; CHOL, JUNG SIK (2016)
The present invention relates to a vertical and inclined explosion protection elevator for an offshore plant, which is applied to various offshore plant structures such as drillship, a semi-submerged drill rig, a fixed platform, and a floating platform. A moving section of the elevator transporting people and objects in the offshore structure in which a frame and a truss are complexly combined cannot be formed in a straight line shape. The elevator moves as the moving section is divided into multiple sections in accordance with a property of the each section. So, an inclined section and a vertical section are compositely formed in the elevator. A movement of the elevator in the inclined section is performed by a rack-pinion method, and the movement of the elevator in the vertical section is performed in a wire-rope method. An inclined section moving unit required to move in the inclined section can be separated from an elevator main body to improve efficiency of the movement in the inclined section and the vertical section. As a main rope is connected to an upper end of the elevator main body by a hinge method, the stability of the elevator main body is prevented from deteriorating due to an inclined movement. Also, a unit weak to explosion in the inclined section and the vertical section is installed in an explosion resistant chamber formed of a metal material with a predetermined thickness and greater to be protected from the explosion. 본 발명은 드릴십, 반잠수식 드릴 리그, 고정식 플랫폼, 부유식 플랫폼 등 다양한 해양 플랜트 구조물에 적용되는 수직 경사형 해상구조물용 방폭형 엘리베이터에 관한 발명이다. 통상적으로 프레임과 트러스가 복잡하게 엮여져 있는 해상구조물에서 사람 및 물건을 이송하는 엘리베이터의 이동 구간은 하나의 직선형태로 만들어질 수 없고, 각 구간의 특성에 따라 여러 구간으로 나누어 이동하게 되므로 본원에서는 경사구간과 수직구간이 복합적으로 이루어진 엘리베이터를 구성한다. 이때, 경사구간에서 엘리베이터의 이동은 랙-피니언 방식으로 수행하며, 수직구간에서 엘리베이터의 이동은 와이어-로프 방식으로 수행하게 된다. 경사구간과 수직구간에서 이동의 효율성을 향상시키기 위하여 경사구간의 이동에 필요한 경사구간 이동부는 엘리베이터 본체와 결합분리 가능하도록 구성하고, 엘리베이터 본체부의 상단에는 주로프가 힌지방식으로 결합되어 경사 이동으로 인한 엘리베이터 본체부의 안정성이 저하되는 것을 방지하는 것을 특징으로 한다. 또한, 경사구간 및 수직구간에서 폭발에 취약한 구성은 일정 두께 이상의 금속재질로 이루어진 방폭챔버 내부에 구비하여 폭발로부터 약한 구성을 보호하는 것을 특징으로 한다.